ナンキョク ノ センルイ チュウ ノ タンカスイソ ステロール オヨビ ヒドロキシ サン - 松本, 源喜; マツモト, ゲンキ; 神田, 啓史; カンダ, ヒロシ; Matsumoto, Genki I.; Kanda, Hiroshi (1985)
P(論文) 南極南ビクトリアランドのマイヤーズ谷, ロス島およびベストフォールドヒルズから得られた蘚類, Pottia heimii, Sarconeurum glaciale, Bryum pseudotriquetrum中の炭化水素, ステロールおよびヒドロキシ酸を測定した。n-アルカン(n-C_<15>-n-C_<33>), アルケンならびにトリテルペン炭化水素(C_<30>H_<50>)が検出された。ステロールは7種類が同定され, 24-メチルおよび24-エチルコレスト-5-エン-3β-オールが主成分(>85%)であった。2-, 3-, ω-1-, ω-ヒドロキシそれに9,16-, 10,16-ジヒドロキシ酸が検出された。9,16-または10,16-ジヒドロキシヘキサデカン酸がもっとも卓越していた。ステロール組成は蘚の種類による差異は小さいが, 炭化水素とヒドロキシ酸組成は試料間で大きく異なり, 生育環境や共存微生物の影響が示唆された。一方, これらのステロールおよびジヒドロキシ酸は, 南極における蘚類の生物地球化学的指標化合物として重要と考えられる。 Hydrocarbons, sterols and hydroxy acids were studied in Antarctic mosses, Pottia heimii, Sarconeurum glaciale and Bryum pseudotriquetrum, to characterize their composition and to find their biogeochemical markers, collected from the Miers Valley of southern Victoria Land, Hut Point Peninsula of Ross Island and Vestfold Hills of Queen Elizabeth Land. Hydrocarbons ranging from C_<15> to C_<33>, including n-alkanes, alkenes and a triterpene (C_<30>H_<50>) were found in the mosses. Four stenols and 3 stanols were identified. The major sterols were 24-methyl- and 24-ethylcholest-5-en-3β-ols, constituting more than 85% of the total sterols in all the mosses. 2-, 3-, ω-1-, ω-hydroxy and 9,16- and 10,16-dihydroxy acids were identified or suggested to be present. The most prominent hydroxy acid was 9,16- or 10,16-dihydroxyhexadecanoic acid. The sterol composition of P. heimii was similar to those of S. glaciale and B. pseudotriquetrum. However, those of hydrocarbons and hydroxy acids differ considerably in the moss samples, suggesting the influences of environmental conditions and microorganisms contained as impurities. On the other hand, high abundances of 24-methyl- and 24-ethylcholest-5-en-3β-ols, along with the dominance of 9,16- or 10,16-dihydroxyhexadecanoic acid, may be useful indicators of mosses in soil, water and sedimentary environments of Antarctica. departmental bulletin paper